Differential diagnosis of frontotemporal dementia - a case report - Talarowska, Monika; Orzechowska, Agata; Karlińska, Iwona; Chamielec, Marcelina; Gałecki, Piotr (Current Problems of Psychiatry, 2012)
Frontotemporal dementia is a progressive disease, a heterogeneous etiology, in which neurodegenerative changes are located in the frontal lobes and temporal lobes. It occurs from 5 to 7 times less frequently than dementi in Alzheimer disease, representing approximately 10-15% of all dementia. The clinical picture fronto-temporal dementia symptoms predominate in the form of neuropsychiatric symptoms of affective, behavioral and personality changes that lead mainly to the disruption of social contacts. Cognitive dysfunction, leading to an (executive), followed later in the disease. In addition, typical for this type of dementia, are disorders of speech in the form of its gradual reduction, verbal stereotypies and perseveration. The aim of the present description of the event was to demonstrate the difficulties associated with differential symptoms of fronto-temporal dementia from symptoms of psychotic disorders and show a progressive deterioration in cognitive function psychological test results.